Definition of the dominating investment directions of development of the company. Part 2 - Z. V. Gorbunova; N. G. Urazov (Вестник СибАДИ)
The article considers the process of detection of the dominant investment area for the development of companies (in the example of the «Irkutskenergo» company). Authors suggested specific industry criteria of marking in investment areas and projects. They presented results of using mathematical methods and decision theory methods for choice of dominant investment area for the development of company. Authors suggested worked out the methodical approach of the forming of projects’ portfolio of the dominant investment area for the development of the «Irkutskenergo» company.